A Recent and Advanced Approach to Traditional Round Robin CPU Scheduling Algorithm to Prioritize Processes with Residual Burst Time Nearest to the Specified Time Quantum - Mythili Boopathi; Pranav Korde; Pallav Dey (Advanced Aspects of Engineering Research Vol. 4, 2021)
The purpose of this paper is to introduce an optimised variant to the round robin scheduling algorithm. Every algorithm works in its own way and has its own merits and demerits. The proposed algorithm overcomes the shortfalls of the existing scheduling algorithms in terms of waiting time, turnaround time, throughput and number of context switches. The algorithm is pre-emptive and works based on the priority of the associated processes. The priority is decided on the basis of the remaining burst time of a particular process, that is; lower the burst time, higher the priority and higher the burst time, lower the priority. To complete the execution, a time quantum is initially specified. In case if the burst time of a particular process is less than 2X of the specified time quantum but more than 1X of the specified time quantum; the process is given high priority and is allowed to execute until it completes entirely and finishes. Such processes do not have to wait for their next burst cycle. In the proposed algorithm, the CPU utilization, throughput and response time is not considered. This algorithm is a basic enhancement to the traditional Round Robin. In the future, the time and space complexity will also be calculated and reduced if required. The working will be enhanced by incorporating Priority based scenario along with Shortest Job First.